2001
DOI: 10.1046/j.1472-765x.2001.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative effect of two lactic acid bacteria strains of human origin on the growth of a myeloma cell line

Abstract: Aims: Twenty lactic acid bacteria strains were isolated from human faeces and tested by MTT assay for stimulation or inhibition of the proliferation of Vero and myeloma cells. Methods and Results: None of the strains significantly affected the proliferation of Vero cells. However, two isolates (HN1 and HA8) showed a strong inhibition of myeloma cell proliferation (16·7 and 5·0%, respectively) by MTT assay. Conclusions: Both strains have an anti‐proliferative effect on a tumoral cell line. Significance and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…At bacterial concentrations of 10 6 -10 7 cfu/mL, a weak inhibition of cellular proliferation (70.9 ± 81.5% of survival) was observed for both strains. However, they displayed a strong inhibitory effect (16.7% and 5% for E. faecium HN1 and L. salivarius HA8, respectively) at a concentration of 10 8 cfu/mL (Zabala et al, 2001). We also observed a dose-dependent response for the antiproliferative abilities of P. pentosaceus, L. plantarum, and W. confusa in our study.…”
Section: Discussionsupporting
confidence: 67%
“…At bacterial concentrations of 10 6 -10 7 cfu/mL, a weak inhibition of cellular proliferation (70.9 ± 81.5% of survival) was observed for both strains. However, they displayed a strong inhibitory effect (16.7% and 5% for E. faecium HN1 and L. salivarius HA8, respectively) at a concentration of 10 8 cfu/mL (Zabala et al, 2001). We also observed a dose-dependent response for the antiproliferative abilities of P. pentosaceus, L. plantarum, and W. confusa in our study.…”
Section: Discussionsupporting
confidence: 67%
“…Leblanc et al 2005;Matsuzaki et al 2007). This activity has been related to the immunomodulatory activity they possess, and likely on the basis of the changes in the cytokine profiles they induce (Zabala et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report, we showed that there was an antiproliferative effect of L. plantarum , Enterococcus faecium and L. salivarius strains isolated from ewe's milk cheese (Haza et al. , 2004) and human faeces (Zabala et al. , 2001a,b).…”
Section: Discussionmentioning
confidence: 99%